Tranexamic acid for reducing blood loss in bipolar transurethral resection of the prostate: a systematic review of literature - Jonathan Doyun Cha; Gabriel Franco de Camargo Galindo; Caroline Vidalli Denser; Carlos Henrique Alves da Silva; Arie Carneiro (Einstein (São Paulo))
ABSTRACT Objective: To study the efficacy of tranexamic acid at reducing bleeding during bipolar prostate resection surgery (B-TURP) in patients with benign prostatic hyperplasia. Methods: We searched registers with MESH terms "prostate hyperplasia," "prostate surgery," and "tranexamic acid." Studies available in full and online, published from 2013 to 2023, in Portuguese, English, Spanish, and French were included; review articles were excluded. Information sources: Portal Regional da Biblioteca Virtual em Saúde and PubMed Central. The Cochrane RoB2 tool was used to analyze risk of bias in randomized clinical trials. Results: Two randomized clinical trials involving 256 patients were included. Both groups had minimal risk of bias. Both studies showed a positive effect of tranexamic acid on blood loss parameters. Only one study in the tranexamic acid group had a lower transfusion rate, and another had a lower irrigation fluid volume and operation time in the tranexamic acid group. A meta-analysis was not performed because of the limited number of eligible studies. Conclusion: For patients undergoing B-TURP for benign prostatic hyperplasia symptoms, the use of tranexamic acid reduced blood loss. However, a limited number of patients were studied, and the available randomized clinical trials presented conflicting conclusions. Therefore, further studies are needed to explore this aspect in detail. Prospero database registration: (www.crd.york.ac.uk/prospero) under registration ID CRD42023416383.